2012
DOI: 10.3748/wjg.v18.i38.5418
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus pre-S2 start codon mutations in Indonesian liver disease patients

Abstract: Pre-S2 start codon mutation was higher in Indonesian patients compared to other Asian countries, and its prevalence was associated with advanced liver disease, particularly in HBeAg⁺ patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The frequencies of mutations at the pre-S2 promoters were significantly higher in the patients with HCC than in the patients without HCC (pre-S2 promoter mutation: 15.3% vs 8.9%, P=0.032) [10]. Furthermore, pre-S2 start codon mutation was associated with advanced liver disease and was the more common type of pre-S mutation in Indonesian patients regardless of the HBV genotype [15,16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of mutations at the pre-S2 promoters were significantly higher in the patients with HCC than in the patients without HCC (pre-S2 promoter mutation: 15.3% vs 8.9%, P=0.032) [10]. Furthermore, pre-S2 start codon mutation was associated with advanced liver disease and was the more common type of pre-S mutation in Indonesian patients regardless of the HBV genotype [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Mutations at the BCP region such as A1762T/G1764A and T1753V were found in high prevalence (59.5% and 40.5%, respectively) and were associated with severe liver disease [12]. In a more recent study, the prevalence of pre-S mutation in Indonesian population was also reported [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of pre-S mutations has also been reported (18,19). Nevertheless, the RT region has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Of the Indonesian viruses, some mutations in the HBV genome that are associated with severe liver disease have been reported, including mutations in the basal core promoter region (e.g., A1762T/G1764A and T1753V) (19)(20)(21) and the pre-S region (22,23). Several minor drug-resistant mutations of HBV in Indonesian treatment-naive patients with chronic hepatitis were recently detected using a deep sequencing method (24).…”
mentioning
confidence: 99%